Pendekatan Inklusif Dakwah Islam Dalam Pendidikan Kewarganegaraan Perspektif Al-Qur’an - Mukzizatin, Siti; Umar, Nasaruddin; Saihu, Made (Jurnal Global Ilmiah, 2025)
This study examines the inclusive approach in Islamic preaching in the context of civic education based on the perspective of the Qur'an. Inclusive preaching emphasizes tolerance, dialogue, and respect for diversity, so that it can contribute to building a harmonious national and state awareness. This study uses a qualitative method based on literature to analyze how the values of inclusive Islamic preaching can be applied in civic education to form a moderate and civilized society. The results of the study indicate that the inclusive approach in preaching is in line with the teachings of the Qur'an on brotherhood, justice, and deliberation, which are important in instilling national values. These findings are expected to be a reference for educators and preachers in developing a more humanistic civic learning model based on Islamic values.